(untitled) (Castilla. Estudios de Literatura, 2021)
The poetry of Javier Sologuren (Lima, 1921-2004), a fundamental author of twentieth-century Peruvian letters, is characterized by its constant expressive renewal. His second booklet of poems, Detenimientos (1948), is born from the reworking of the principles of his previous writing, and outlines some features that characterizes his later work. However, critics have only touched on it briefly. This article offers a look at the aesthetic proposal of the booklet. Through the stylistic analysis and the interpretation of the poems, the conception of lyricism, the vision of the world and the sensibility of the lyrical speaker and the expressive principles that give Detenimientos unity and solidity are investigated.